Analysis of relationships between molecular distances and heterosis of F1 performance in Brassica Napus L - XU Xiao-dong; CHEN Fei; NI Xi-yuan; ZHANG Xiao-wei; ZHAO Jian-yi (浙江大学学报. 农业与生命科学版)
Genetic diversity among 38 oilseed rape (Brassica napus L.) cultivars originated from China, European and Canada were evaluated using random amplified polymorphic DNA (RAPD) markers. Nine representative cultivars and their 36 F1 hybrids, obtained by half diallel cross design, were used to analyze the relationship between molecular distances and yield heterosis. The results showed that 97 polymorphic bands were obtained from 18 RAPD primers, and cluster analysis classified these 38 cultivars into 4 clear-cut groups. Correlation analysis indicated that genetic distance was no significant positive correlation with mid-parent heterosis (MP), over-parent heterosis (HP) and yield per plant among 36 F1 combinations. However, when dividing them into 10 combination types according to dendrogram of parents, it was revealed that genetic distances were highly significantly correlated with MP (r=0.789, P <0.01), HP (r=0.659, P <0.05), respectively, and there was also positive correlation between yield per plant and HP at P<0.05 level. In addition, most China/European F1 hybrids had more visible heterosis and higher yield performance than other combination types, especially in those produced from China/European-spring crosses. Dissection of yield heterosis for the top 10 F1 hybrids disclosed that 9 and 8 combination exhibited the positive heterosis of siliques per plant and 1 000- seeds mass, respectively, while 4 combination showed complementary relationships between seeds per silique and 1 000-seeds mass. These results indicate that it is not sufficient to accurately predict heterosis and yield performance alone according to molecular distance between parental lines. It is more possible to achieve successful F1 hybrids in China/European crosses. Comprehensively considering heterosis, yield performance, seed quality and growth habit, it might be prior suggested to choose spring type rapeseed cultivars from European or Canada as parental or breeding materials in rapeseed hybrid developments in China. In addition, the combination types of the significantly positive heterosis of siliques per plant and 1 000-seeds mass, or strong complementary heterosis between seeds per silique and 1 000-seeds mass were recommended to obtain high yield of F1 hybrids.